1983
DOI: 10.1055/s-2007-1021548
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Ovarian Dermoid Cyst with Malignant Transformation Perforated into the Rectosigmoid Colon and Small Intestine

Abstract: A 72-year-old female was admitted to hospital with diarrhea containing hair. The abdominal plain film showed teeth-like structures in the right lower quadrant. Barium enema and endoscopic examination were performed, and the results indicated a possible dermoid cyst perforated into the rectosigmoid colon and small intestine. The operation revealed a dermoid cyst of the right ovary perforated into the rectosigmoid colon and small intestine. Histopathologically, a dermoid cyst and in part well-differentiated squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…In addition, there were intra-operative features of peritonitis also. Although such an occurrence has been described previously in association with malignant transformation, 9,11,14 macro and microscopic examination confirmed that this was not the case here and that the cyst had directly infiltrated the bowel wall causing intraluminal obstruction in the form of a pedunculated tumor. It seems probable that a similar mechanism to that proposed for fistula formation had occurred, possibly precipitated by the recent pregnancy.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, there were intra-operative features of peritonitis also. Although such an occurrence has been described previously in association with malignant transformation, 9,11,14 macro and microscopic examination confirmed that this was not the case here and that the cyst had directly infiltrated the bowel wall causing intraluminal obstruction in the form of a pedunculated tumor. It seems probable that a similar mechanism to that proposed for fistula formation had occurred, possibly precipitated by the recent pregnancy.…”
Section: Discussionmentioning
confidence: 68%
“…8 In contrast, rupture, infection and secondary malignant change are uncommon complications and dermoid cysts only very rarely present with bowel involvement. In this regard, entero-ovarian fistulae have been described involving both the small [9][10][11] and large [12][13][14][15] bowel. Such patients may present with pain, rectal bleeding or the passage of dermoid cyst contents such as hair and teeth within the stool.…”
Section: Discussionmentioning
confidence: 99%
“…4 There is only one previous report of an ovarian teratoma with fistulae to both the small and large bowel simultaneously, as was seen in our patient. 5 However, in that case, the ovarian teratoma had malignant components, a finding not noted in the final pathology of our specimen.…”
Section: Commentmentioning
confidence: 82%
“…3 It is important to note that such rare findings associated with teratomas may suggest malignancy. 5 Surgeons should be prepared to perform staging surgery in the event that malignancy is identified on rapid frozen section evaluation. 6 …”
Section: Commentmentioning
confidence: 99%
“…Th e treatment of teratomas is surgical (salpingo-oophorectomy or resection of the ovary), and depends upon the age of the patient and the volume of the tumor. Immature teratomas are treated by a combination of surgery and multimodal chemotherapy 3,5,6 . Th e aim of this study was to determine the number of ovarian teratomas in the routine biopsy material received and diagnosed at Ljudevit Jurak Clinical Department of Pathology, Sestre milosrdnice University Hospital Center during a 5-year period, as well as their clinical, gross and microscopic characteristics.…”
Section: Introductionmentioning
confidence: 99%